Efforts to standardize wildlife toxicity values remain unrealized. (4th December 2012) - Mayfield, David B; Fairbrother, Anne
Abstract Wildlife toxicity reference values (TRVs) are routinely used during screening level and baseline ecological risk assessments (ERAs). Risk assessment professionals often adopt TRVs from published sources to expedite risk analyses. The US Environmental Protection Agency (USEPA) developed ecological soil screening levels (Eco‐SSLs) to provide a source of TRVs that would improve consistency among risk assessments. We conducted a survey and evaluated more than 50 publicly available, large‐scale ERAs published in the last decade to evaluate if USEPA's goal of uniformity in the use of wildlife TRVs has been met. In addition, these ERAs were reviewed to understand current practices for wildlife TRV use and development within the risk assessment community. The use of no observed and lowest observed adverse effect levels culled from published compendia was common practice among the majority of ERAs reviewed. We found increasing use over time of TRVs established in the Eco‐SSL documents; however, Eco‐SSL TRV values were not used in the majority of recent ERAs and there continues to be wide variation in TRVs for commonly studied contaminants (e.g., metals, pesticides, PAHs, and PCBs). Variability in the toxicity values was driven by differences in the key studies selected, dose estimation methods, and use of uncertainty factors. These differences result in TRVs that span multiple orders of magnitude for many of the chemicals examined. This lack of consistency in TRV development leads to highly variable results in ecological risk assessments conducted throughout the United States. Integr Environ Assess Manag 2013; 9: 114–123. © 2012 SETAC